2015
DOI: 10.1089/jwh.2014.4980
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Device Therapy for Heart Failure: Utilization, Outcomes, and Adverse Events

Abstract: Our review confirms women are markedly underrepresented in CRT trials, and when a CRT device is implanted, women have a therapeutic response that is equivalent to or better than in men, while there is no difference in adverse events reported by sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 124 publications
(149 reference statements)
2
12
1
Order By: Relevance
“…This resulted in near identical survival between groups based on factors traditionally thought to worsen outcomes in cardiovascular conditions. A similar phenomenon has been reported in a systematic review of cardiac resynchronization therapy trials—although women are markedly under‐represented in cardiac resynchronization therapy trials, when a cardiac resynchronization therapy device is implanted, women have a therapeutic response that is equivalent to or better than in men. Similarly, despite lower rates of ICD implantation in women in the USA compared with men, it has been shown that when access to treatment and counselling around ICD implantation is equal between the sexes, rates of ICD implantation are also equal …”
Section: Discussionsupporting
confidence: 74%
“…This resulted in near identical survival between groups based on factors traditionally thought to worsen outcomes in cardiovascular conditions. A similar phenomenon has been reported in a systematic review of cardiac resynchronization therapy trials—although women are markedly under‐represented in cardiac resynchronization therapy trials, when a cardiac resynchronization therapy device is implanted, women have a therapeutic response that is equivalent to or better than in men. Similarly, despite lower rates of ICD implantation in women in the USA compared with men, it has been shown that when access to treatment and counselling around ICD implantation is equal between the sexes, rates of ICD implantation are also equal …”
Section: Discussionsupporting
confidence: 74%
“…The QRSd of 114 ms was a cutoff for predicting CRT responders, with an area under the curve (AUC) of 0.62 be shorter than those of Westerners and, by extension, we suspected that the indication for CRT in Japanese patients would be a shorter QRSd. Interestingly, several studies in which responses to CRT have been assessed in relation to the patients' sex have shown better responses to CRT among women than among men [15][16][17][18][19][20]. Our present investigation did not reveal a significant difference in the CRT response between the men and women.…”
Section: Discussioncontrasting
confidence: 54%
“…This trend has been consistent over the past three decades [26]. .This disparity remained even after adjusting for the lower incidence of CHF in women.…”
Section: Gender Differences In Crt Utilizationsupporting
confidence: 60%